2020
DOI: 10.1007/s00167-020-05873-1
|View full text |Cite
|
Sign up to set email alerts
|

Lower donor-site morbidity using QT autografts for ACL reconstruction

Abstract: Purpose Comparing scar cosmesis and regional hypoesthesia at the incision site between quadriceps tendon (QT), bone–patellar tendon–bone (BPTB), and hamstring tendon (HT) for anterior cruciate ligament (ACL) reconstruction. Methods Ninety patients undergoing ACL reconstruction with QT, HT or BPTB were evaluated at 1‐year post‐op. Scar cosmesis was assessed using the patient and observer scar assessment scale (POSAS) and length of the incision. Sensory outcome was analyzed by calculating the area of hypoesthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 50 publications
1
35
0
Order By: Relevance
“…There were 15 studies [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] (Level of evidence I: 3; II: 2; LOE III: 10) comparing 611 patients with QT to 543 patients with HS, with a mean follow-up time of 27.4 months. The mean age was 27.9, and 71.1% were male.…”
Section: Study Characteristics and Patient Demographicsmentioning
confidence: 99%
“…There were 15 studies [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] (Level of evidence I: 3; II: 2; LOE III: 10) comparing 611 patients with QT to 543 patients with HS, with a mean follow-up time of 27.4 months. The mean age was 27.9, and 71.1% were male.…”
Section: Study Characteristics and Patient Demographicsmentioning
confidence: 99%
“…Systematic reviews comparing QT/QTPB autografts with other types of autografts suggested that the former type provide comparable clinical and functional outcomes, but with reduced donor-site pain. 2 , 13 , 14 , 18 Other comparative studies also advocated the use of QT/QTPB autografts due to the lower rates of sensory loss, 12 stronger extensor mechanism, 1 and superior biomechanical characteristics. 16 Fu et al 4 reported 5 cases of patella fracture (among 57 patients) after harvesting QTPB autografts proposing a problem specific to the graft; similarly, 6 cases of patella fracture (4 intraoperatively and 2 postoperatively) occurred in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…It was therefore possible to separate the patients into 4 groups: (1) single-strand quadrupled semitendinosus ACLR without LET (ST4 group) (n = 55), (2) ST4 with additional anatomic LET using the same hamstring graft (ST4+LET group) (n = 77) , (3) bone–patellar tendon and LET (BTB+LET group) (n = 43), and (4) quadriceps tendon and LET (QT+LET group) (n = 91). 24…”
Section: Methodsmentioning
confidence: 99%